Effect of curcumin on circulating interleukin-6 concentrations: A systematic review and meta-analysis of randomized controlled trials. (September 2016) - Derosa, Giuseppe; Maffioli, Pamela; Simental-Mendía, Luis E.; Bo, Simona; Sahebkar, Amirhossein
Graphical abstract: Abstract: The aim of this meta-analysis was to evaluate the efficacy of curcuminoids supplementation on circulating concentrations of IL-6 in randomized controlled trials (RCTs). The search included PubMed-Medline, Scopus, Web of Science and Google Scholar databases by up to November 01, 2015, to identify RCTs investigating the impact of curcuminoids on circulating IL-6 concentrations. Nine RCTs comprising 10 treatment arms were found to be eligible for the meta-analysis. There was a significant reduction of circulating IL-6 concentrations following curcuminoids supplementation (WMD: −0.60 pg/mL, 95% CI: −1.06, −0.14, p  = 0.011). Meta-regression did not suggest any significant association between the circulating IL-6 lowering effects of curcuminoids with either dose or duration of treatment. There was a significant association between the IL-6-lowering activity of curcumin and baseline IL-6 concentration (slope: −0.51; 95% CI: −0.80, −0.23; p = 0.005). This meta-analysis of RCTs suggested a significant effect of curcumin in lowering circulating IL-6 concentrations. This effect appears to be more evident in patients with higher degrees of systemic inflammation.